Feasibility of Immunohistochemical p16 Staining in the Diagnosis of Human Papillomavirus Infection in Patients With Squamous Cell Carcinoma of the Head and Neck: A Systematic Review and Meta-Analysis - Wang, Huanhuan; Zhang, Yuyu; Bai, Wei; Wang, Bin; Wei, Jinlong; Ji, Rui; Xin, Ying; Dong, Lihua; Jiang, Xin (Frontiers in Oncology, 2020)
Abstract: Human papillomavirus (HPV) is a risk factor for squamous cell cancers of the head and neck (HNSCC). However, no specific test has been identified as the gold standard for diagnosing HPV infections. This study aimed to investigate the feasibility of IHC-p16 as an alternative modality for diagnosing HPV infection. We searched PubMed, EMBASE, Web of Science, and Cochrane library for studies that evaluated the diagnostic accuracy of IHC-p16 staining. A total of 30 studies involving 2,963 patients were included. The combined sensitivity was 0.94 (95% CI: 0.92-0.95); specificity, 0.90 (95% CI: 0.89-0.91); positive likelihood ratio (LR), 6.80 (95% CI: 5.63-8.21); negative LR, 0.10 (95% CI: 0.07-0.16); diagnostic odds ratio, 85.98 (95% CI: 55.57-133.03); and area under the curve value, 0.9550. Subgroup analysis showed that the IHC-p16 test was more consistent with the in situ hybridization (ISH) test and has greater diagnostic value for oropharyngeal squamous cell carcinoma. The diagnostic efficacy of IHC-p16 varied among countries. In conclusion, IHC-p16 has high sensitivity and specificity for diagnosing HPV infection in HNSCC. The consistency of IHC-p16 findings with those of ISH indicate that their combination can be used to improve the specificity of diagnosis.